2016
DOI: 10.1186/s12885-016-2468-x
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of DNMT 3B promotes epithelial-mesenchymal transition and gene expression profile of invasive head and neck squamous cell carcinomas cell lines

Abstract: BackgroundThe 5-year overall survival rates for head and neck cancer (HNC) relies on distant metastasis. Importantly, the epithelial-mesenchymal transition (EMT) is believed to be an initial step of metastasis. However, the relationship of epigenetic with EMT formation is still unexplored in HNC. This study focuses on invasive subclones of HNC cell lines through the simulation of invasion in vitro; and underlying mechanisms were analyzed including DNA methylation and gene expression profile.MethodsInvasive sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 84 publications
(92 reference statements)
0
33
0
Order By: Relevance
“…Nevertheless, Tang and others (Tang et al, 2014) had shown that the mechanism which contributes to breast cancer may be the effect of miR-185 on E2F6, DNMT1 and BRCA1. Moreover, DNMT3B and DNMT3B can reduce the level of E-cadherin expression (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Tang and others (Tang et al, 2014) had shown that the mechanism which contributes to breast cancer may be the effect of miR-185 on E2F6, DNMT1 and BRCA1. Moreover, DNMT3B and DNMT3B can reduce the level of E-cadherin expression (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies on CFTR in other cancers, lead to a hypothesis that CFTR might be deeply related to metastasis, poor prognosis, or even poor survival rates. Five-year survival rates for HNC patients with metastasis are extremely low, at about 10%, while rates for other HNC patients are about 50% [62]. The addressing of these challenges by early diagnosis of HNC and the definition of HNC metastasis indicators is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA‐29b may also controls tumor microenvironment by targeting prometastatic regulators, which are involved in angiogenesis, collagen remodeling, and proteolysis. Moreover, it is also recently reported that the use of miRNA‐29b mimic in HNSCC/OSCC cell lines downregulates DNA methyltransferase 3 beta and inhibits epithelial‐mesenchymal transition and cell invasion …”
Section: Micrornas Regulate Epithelial‐mesenchymal Transition In Oralmentioning
confidence: 97%
“…Accumulating evidence suggests a critical role of miRNAs in the regulation of epithelial‐mesenchymal transition and epithelial‐mesenchymal transition‐related malignant phenotypes in OSCC . The most relevant altered miRNAs in OSCC that are related to epithelial‐mesenchymal transition are summarized in Table …”
Section: Micrornas Regulate Epithelial‐mesenchymal Transition In Oralmentioning
confidence: 99%
See 1 more Smart Citation